Identification and Validation of Novel Subtype-Specific Protein Biomarkers in Pancreatic Ductal Adenocarcinoma. Issue 3 (March 2017) - Kuhlmann, Laura; Nadler, Wiebke M.; Kerner, Alexander; Hanke, Sabrina A.; Noll, Elisa M.; Eisen, Christian; Espinet, Elisa; Vogel, Vanessa; Trumpp, Andreas; Sprick, Martin R.; Roesli, Christoph P.
Abstract : Objectives: Pancreatic ductal adenocarcinoma (PDAC) has been subclassified into 3 molecular subtypes: classical, quasi-mesenchymal, and exocrine-like. These subtypes exhibit differences in patient survival and drug resistance to conventional therapies. The aim of the current study is to identify novel subtype-specific protein biomarkers facilitating subtype stratification of patients with PDAC and novel therapy development. Methods: A set of 12 human patient-derived primary cell lines was used as a starting material for an advanced label-free proteomics approach leading to the identification of novel cell surface and secreted biomarkers. Cell surface protein identification was achieved by in vitro biotinylation, followed by mass spectrometric analysis of purified biotin-tagged proteins. Proteins secreted into a chemically defined serum-free cell culture medium were analyzed by shotgun proteomics. Results: Of 3288 identified proteins, 2 pan-PDAC (protocadherin-1 and lipocalin-2) and 2 exocrine-like-specific (cadherin-17 and galectin-4) biomarker candidates have been validated. Proximity ligation assay analysis of the 2 exocrine-like biomarkers revealed their co-localization on the surface of exocrine-like cells. Conclusions: The study reports the identification and validation of novel PDAC biomarkers relevant for the development of patient stratification tools. In addition, cadherin-17 and galectin-4 may serve as targets for bispecific antibodies as novel therapeutics in PDAC.